Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Vania, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this research is to examine the effect offirm size, net working capital, cash conversion cycle, cash flow, and leveragetoward cash holding of manufacturing company listed in Indonesia Stock Exchange on 2015-2017. This research used non-probability sampling method with purposive sampling technique. The number of samples used in this research was64 manufacturing firms. The result show that net working capital and leveragehave a negative impact toward cash holding. Firm size, cash conversion cycle, andcash flow have no impact toward cash holdings. The result also shows thatfirm size, net working capital, cash conversion cycle, cash flow, and leverage simultaneously have impact toward cash holding